HIPERTENSI, AKTIVITAS FISIK, INDEKS MASSA TUBUH (IMT) DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS DI BULELENG - Mahaguna Putra, Made; Sudiharto, Sudiharto; Marleni, Devy; Suarjana, I Ketut (Journal of Nursing and Midwifery Sciences, 2023)
Diabetes Mellitus and Hypertension is a common condition that often arises together, both diseases are considered as the risk of cardiovascular disease and microvascular complications of many factors that influence it like bad lifestyle changes. This study aims to determine the relationship between hypertension, physical activity, and body mass index with blood sugar levels in Diabetes Mellitus patients at Public Health Center in Buleleng. This research uses a quantitative research design cross-sectional method with a simple random sampling technique with 150 samples, taken by observation, and observation is guided by the Baecke questionnaire. Data analysis with Spearman Rank correlation test shows no relationship between hypertension with blood sugar levels with value ρ = (0.938)> α (0.05), no relationship between physical activity with blood sugar level body mass index with blood sugar level with value ρ = (0.914)> α (0.05). There is no relationship between hypertension, physical activity, and body mass index with blood sugar levels in Diabetes Mellitus patients